Risk Analysis of Housing Projects in Malaysia Using an Industrialised Building System - Abu Hasan Sazalli, Saiful Azri (2008)
The use of industrialised building system (IBS) has attracted many countries like Singapore, Sweden, Germany, and Japan. This system can replace the conventional building system that uses labour intensive force. However, although this system has been used since 1964, its acceptance in Malaysia among constructors is not satisfactory due to its failure in managing the construction system risks. Therefore in order to address this issue, this study has identified risks faced by developers in housing projects that use industrialised building system. The study also identifies highly risked construction stages, determines risk allocation for sources of risk, and proposes a computer program for the risk management. The techniques to identify risks being used in this study are through analysis of past research publications like journal, conference and discussion with parties involves in construction industry. Data is compiled through questionnaires that are distributed and collected from housing developers. The data is then analysed using statistical techniques like Chi- Square Test and Pearson Correlation Coefficient. It is found that there are twenty eight sources of risk that contribute to six types of risk in construction project. The top five sources of risk are inexperienced contractor in IBS project, complexity in design, contractor performance failure, inappropriate estimate of construction cost, and variety of design. Based on four stages of construction which are the initial stage, tendering stage, procurement stage and implementing stage; initial stage contributes to the highest risk in industrialized building system. The problem of quality, poor productivity, defective materials, labour disputes and loss or delay due to resources availability are on contractors’ shoulder. The building owners are responsible on variation of work, sales and marketing, and deficiencies in specification and drawing. The result of this study reveals that there is no relation between types of industrialized building system being used and types of risk. Three categories of risk which are financial risk, construction risk and design risk are interrelated with each other. A tentative risk register tool produced in this study is based on computer application. It may help developers to identify sources of risk, evaluate and manage the identified risks as part of decision making. In conclusion, it is hoped that this study could help developers in making risk management planning besides improving decision making and achieving project objectives.